Criminal Responsibility of Children Who Are Bullying That Results in Serious Injury - Utari Debora; Abdul Rahman Maulana Siregar; Rahmayanti Rahmayanti (CV. Era Digital Nusantara, 2026)
Criminal liability for children who perpetrate bullying resulting in serious injury is an increasingly prominent issue with the rise in cases of violence between children. The focus of this research is on Indonesian legal regulations, the application of criminal sanctions, and the age limit for criminal liability under the Juvenile Criminal Justice System Law. This research uses a normative juridical method by examining laws and regulations, literature, and related cases. The findings in this discussion indicate that bullying resulting in serious injury can be classified as a crime with criminal consequences or actions, but its implementation must still consider the principle of the child's best interests. Diversion can only be implemented if the crime is not categorized as serious, so in cases of serious injury, diversion opportunities are limited. This research emphasizes the importance of a proportional and recovery-oriented approach for both perpetrators and victims to ensure the achievement of the goals of child development and protection in the criminal justice process.